Endoscopic submucosal dissection of colorectal pedunculated polyps - Jakobs, Johanna Katharina; Zumblick, Malte; von Gerlach, Susanne; Stathopoulos, Petros; Glas, Sebastian; Denkert, Carsten; Denzer, Ulrike Walburga (Endoscopy International Open, 2024)
Background and study aims For pedunculated colon polyps, en bloc resection with inclusion of the polyp stalk is necessary to yield an accurate histologic staging. This can be challenging in cases of a large polyp and/or broad stalk using conventional snare resection. We evaluated the feasibility of endoscopic submucosal dissection (ESD) for large pedunculated polyps with broad stalks.Patients and methods Between February 2019 and November 2021 all patients with large pedunculated polyps defined as polyp diameter ≥ 20 mm and or a broad stalk > 5 mm were enrolled in the study. All polyps were resected in ESD technique with dissection of the polyp stalk at the base after injection.Results Twenty-five patients (male = 18, age mean: 67 years) were included. En bloc resection was achieved in 100% of the patients (25/25 polyps). Polyps were mainly located in the sigmoid (n = 19) and rectum (n = 3). Median polyp size was 30×25×17 mm. Histologic examination revealed the following results: adenoma low-grade intraepithelial neoplasia (LG-IEN): nine; high-grade intraepithelial neoplasia (HG-IEN): seven; pTis: three; adenoarcinoma: five (G1, pT1, L0, V0, Haggitt 3: 2/G2, pT1, L0, V0, Haggitt 3:2/G3, pT1, Bd3, V1, Haggitt 4: 1); other: 1.R0 resection rate was 100% and the curative resection rate yielded 96% (24/25) without severe adverse events.Conclusions ESD achieved high en bloc and R0 resection rates for large pedunculated polyps. In our collective, up to 32% of polyps already had adenocarcinoma, resulting in a high curative resection rate due to complete resection and subsequently accurate risk classification.
Keywords: Endoscopy Lower GI Tract; Polyps / adenomas / ...; Colorectal cancer; Endoscopic resection (polypectomy, ESD, EMRc, ...); CRC screening